Food Insecurity, Financial Shocks, and Financial Coping Strategies among Households with Elementary School Children in Wisconsin. Issue 3 (16th November 2017) - Bartfeld, Judith; Collins, J. Michael
Abstract : This article examines the associations among food insecurity, financial shocks, and financial coping strategies among elementary school students' households in Wisconsin using a survey of parents. Volatility in income and expenses are predictive of households' ability to meet food needs, and parents who have experienced large or volatile expenses report more difficulty in shielding child(ren) from food hardships. Food insecurity is characterized by a continuum of financial adaptations—ranging from relying on savings, borrowing from family and friends, and increased work effort in conjunction with marginal food security, and progressing toward use of potentially inferior forms of credit such as payday and pawn loans at the more severe end of the food insecurity spectrum. In addition to income‐focused coping strategies, survey respondents report food‐specific coping strategies. Overall, the results suggest that food security and financial security interventions may work in concert and may benefit from greater coordination.